Southeast Asian education in modern history schools, manipulation, and contest - Jolliffe, Pia; Bruce, Thomas Richard (Abingdon, Oxon, [England] Routledge, an imprint of the Taylor & Francis Group, 2019)
"Social, political and economic change in Southeast Asia of the last two hundred years has been faster and more substantial than in any previous age as the impact of the Industrial Revolution intruded into the region and, particularly over the last fifty years, manifested itself in patent and tangible measures of the region's productivity reflecting unprecedented sustained economic growth. This book analyses the Southeast Asian experience of educational development. Through a variety of micro-historical studies on the subject of education, policy and practice in the region from the emergence of modern education to the end of the twentieth century, the book examines if there is an identifiably distinct Southeast Asian approach to the provision of education. Contributors focus on issues connected to schools and modernity, schools and politics, schools and the actions of Western teachers in the region. They also explore the extent to which contest over educational content in schools has occurred and establish the particular socio-cultural, political and economic bases upon which these contestations have played out. Demonstrating that education has been facilitated by the region's particular configurations, its unique demographic, religious, social, environmental, economic and political context, the book presents the obstacles that have prevented education making as full an impact on the region's rate of change. An analysis of the history of schools in Southeast Asia, this book offers a valuable explanation of the current state of education in Southeast Asia and the challenges it has inherited. This book will be of interest to academics in the field of Southeast Asian Studies, Asian Studies, education, nationalism, and history."--Provided by publisher.
Introduction / Pia M. Jolliffe and Thomas Richard Bruce -- Myanma Identity and the Shifting Value of the Classical Past: A Case Study of King Kyansittha in Burmese History Textbooks, 1829-2017 / Rosalie Metro -- The legend of the "lost book" and the Value of Education Among the Karen People in Myanmar and Thailand / Pia Jolliffe -- The Modernisation of Female Education and the Emergence of Class-conflict Between Literate Groups of Women in Siam 1870-1910 / Natanaree Posrithong -- Thailand's Early Adult Education in Textbooks: Inclusion, Exclusion and Literacy, 1940-1944 / Wasitthee Chaiyakan -- Contesting Chinese Education: Schooling in the Kuomintang Chinese Diaspora in Northern Thailand, 1975-2015 / Aranya Siriphon and Sunanta Yamthap -- The Emergence of Vocational Education, Modern Shoemaking and a National Economy in Thailand, 1895-1973 / Thomas Richard Bruce -- V'n qu'c ng: Teaching Modernity through Classics: Women's Education in Colonial Vietnam / Marta Lopatkova -- Tinkering Your Way to Prosperity: Technical Education, Auto-Mechanics and Entrepreneurship in Late-Colonial Vietnam, Erich DeWald -- Despite Education: Malaysian Nationhood and Economic Development in Retrospect, 1874-1970 / Elsa Lafaye de Micheaux -- Full Colour Illustrations: Presentations of Race in Singapore's History Textbooks, 1965-2000 / Theophilus Kwek -- State and Islamic Education Growing into Each Other in Indonesia / Kevin W. Fogg -- American Education in the Philippines and Filipino Values / Jeremiah A. Lasquety-Reyes.
Includes bibliographical references and index.
Keywords: Education -- Southeast Asia -- History; Educational change -- Southeast Asia -- History; Education -- Social aspects -- Southeast Asia